Profil komunikasi matematis siswa SMP pada materi relasi dan fungsi ditinjau dari gaya belajar - Rosita, Martina; Shodiqin, Ali; Prasetyowati, Dina (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2020)
This research aims to know the profile junior high school students mathematics communication viewed from the learning style of the material relations and functions. This research is descriptive qualitative research. Research subject are 6 students of grade VIII MTs. Muhammadiyah Kajen with visual learning style, auditory learning style and kinesthetic learning style. Data collection techniques in the form of written tests and interview. Data validity using triangulation method that is by comparing the results of the written and interview. From the reseach obtained by students with visual learning style can be all indicators of the mathematical communications that is expressing daily events into mathematical language or symbols,explain an idea,situations and mathematical relations with real objects, picture,graphs and algebra,states the situation in the form of an image and compile mathematical model and solve it,states the image in plain language form (arrange story problems) and expressing arguments and reading with the understanding of written mathematical presentation and draw conclutions.Students with an auditory learning style can satisfy the indicators of expressing daily events into mathematical language or symbols, explain an idea, situations and mathematical relations with real objects, picture,graphs and algebra,states the situation in the form of image and compile mathematical model and solve it,and reading with the understanding of written mathematical presentation and draw conclutions. Students with kinesthetic learning style are able to expressing daily events into mathematical language or symbols,reading with the understanding of written mathematical presentation and draw conclutions.